Effect of Acute Exposure of Gamma Rays on Seed Germination and Seedling Growth of Pinus kesiya Gord and P. wallichiana A.B. Jacks - Thapa, C.B. (Our Nature, 2006)
Present study deals with the effect of acute exposure of gamma rays on Pinus kesiya and P. wallichiana. Seeds were eradicated with a 60cobalt sources emitting gamma rays at the rate of 2.8 kR/min. The seeds were given 1.0, 2.5, 5.0, 10.0, 15.0, 20.0 and 30.0 kR exposures. Germination in control and treated seeds of both the species started simultaneously 26 days after sowing. In P. kesiya seeds exposed to 30kR germinated but in P. wallichiana 30 kR was lethal for seed germination and it was restricted up to 20 kR only. With increasing exposure root, hypocotyl and epicotyl elongation decreased in both the species. In P. kesiya more than 50% inhibition was induced by 10 kR but in P. wallichiana this exposure induced 100% inhibition of growth in all the cases. In both the species the intensity of inhibition increased with increasing exposures though lower exposure in some cases was stimulatory. Keywords: Radiation exposure, gamma rays, 60cobalt, intensity, stimulation, inhibition. doi:10.3126/on.v2i1.318 Our Nature (2004) 2: 13-17